COVID-19 in young and middle-aged adults: predictors of poor outcome and clinical differences - Tabernero, Eva; Ruiz, Luis A.; España, Pedro P.; Méndez, Raúl; Serrano, Leyre; Santos, Borja; Uranga, Ane; González, Paula; Garcia, Patricia; Torres, Antoni; Menendez, Rosario; Zalacain, Rafael (Infection, 2022)
Introduction Young and middle-aged adults are the largest group of patients infected with SARS-CoV-2 and some of them develop severe disease. Objective To investigate clinical manifestations in adults aged 18–65 years hospitalized for COVID-19 and identify predictors of poor outcome. Secondary objectives: to explore differences compared to the disease in elderly patients and the suitability of the commonly used community-acquired pneumonia prognostic scales in younger populations. Methods Multicenter prospective registry of consecutive patients hospitalized for COVID-19 pneumonia aged 18–65 years between March and May 2020. We considered a composite outcome of “poor outcome” including intensive care unit admission and/or use of noninvasive ventilation, continuous positive airway pressure or high flow nasal cannula oxygen and/or death. Results We identified 513 patients < 65 years of age, from a cohort of 993 patients. 102 had poor outcomes (19.8%) and 3.9% died. 78% and 55% of patients with poor outcomes were classified as low risk based on CURB and PSI scores, respectively. A multivariate Cox regression model identified six independent factors associated with poor outcome: heart disease, absence of chest pain or anosmia, low oxygen saturation, high LDH and lymphocyte count < 800/mL. Conclusions COVID-19 in younger patients carries significant morbidity and differs in some respects from this disease in the elderly. Baseline heart disease is a relevant risk factor, while anosmia and pleuritic pain are associated to better prognosis. Hypoxemia, LDH and lymphocyte count are predictors of poor outcome. We consider that CURB and PSI scores are not suitable criteria for deciding admission in this population.